Centenary of the approval of the 8-hour Working Time Act - Mora Chinchilla, Carolina (2021)
On December 20, 2020, 100 years of the passage of the 8-hour working day law was fulfilled. During 1920 the strikes and demonstrations were recurring, requested to reduce working hours and a pay increase, until finally the Constitutional Congress of Costa Rica approved it. This work makes a tour of the different events surrounding these labor claims, thus recognizing the advances of national social movements, the development of the press and of course, the political and economic situation of the country, even governed by acting President Francisco Aguilar Barquero, successor to dictator Federico Tinoco. It cannot fail to mention the international situation, which so many economic and international relations problems had brought to the country and the undeniable influence of the various currents of thought and forms of organization coming from Europe and the United States.